ピナトゥボ フンカ ト ショウワキチ ノ キコウ - 金戸, 進; カネト, ススム; Kaneto, Susumu (1997)
P(論文) 南極域における気候変動に関する総合研究(ACR)期間の最終年である1991年は, 6月にフィリピンのピナツボ火山が, 8月にはチリのハドソン火山の噴火がおき, 大量の噴出物が成層圏にまで到達して気候システムは大きな影響を受けた。昭和基地で行われた観測結果を全球などの観測結果と比較して, この影響がどのようなものであったかを見た。噴煙の直接的な影響を受ける混濁度観測や日射観測では1991年末から影響が見られた。しかし, 気温やオゾン全量など大循環の結果のような間接的な要素では, 影響がはっきりしなかったり(成層圏気温), 影響と思われる偏差が見られたものの発現時期に全球とのズレが考えられるもの(地上気温やオゾン全量)があった。 During the last year of the Antarctic Climate Research (ACR) period, two large volcanos erupted. In June 1991,the volcano Pinatubo in the Philippines Islands (15°N, 120°E) erupted and injected a large volcanic cloud in to the lower and middle stratosphere. In August 1991,Mt. Hudson in southern Chile (46°S, 73°W) erupted; its volcanic cloud reached to 18km. From NOAA/AVHRR data, within 1991,the volcanic aerosol of Pinatubo dispersed mainly in tropical latitudes and that of Hudson spread in the area south of 40°S. The eruption effects are investigated here by comparing meteorological observation results at Syowa Station (69°S, 39°E) with global analyses. The optical observations which measure direct effects of eruption materials, show a large effect from late 1991. Abnormal deviations were detected in surface temperature and total ozone amount but the occurrence is retarded relative to global average occurrence. Effects on stratospheric temperature were not detected. departmental bulletin paper